1992
DOI: 10.1128/aem.58.9.2764-2770.1992
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of a locus on the Bacteroides ovatus chromosome which contains xylan utilization genes

Abstract: Bacteroides ovatus, a gram-negative obligate anaerobe found in the human colon, can utilize xylan as a sole source of carbohydrate. Previously, a 3.8-kbp segment of B. ovatus chromosomal DNA, which contained genes encoding a xylanase (xylI) and a bifunctional xylosidase-arabinosidase (xsa), was cloned, and expression of the two genes was studied in Escherichia coli (T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 17 publications
1
21
0
1
Order By: Relevance
“…The relative abundance of Bacteroides ovatus , Bacteroides thetaiotaomicron , Bacteroides cellulosilyticus , and Bacteroides uniformis from genus Bacteroides was significantly higher than that in the control group at the same time point and at 0 hr. Some studies showed that a particular variety of polysaccharides can be fermented by Bacteroides ovatus , Bacteroides thetaiotaomicron , and Bacteroides uniformis (Flint, Scott, Duncan, Louis, & Forano, 2014; Gherardini & Salyers, 1987; Salyers, Vercellotti, West, & Wilkins, 1977; Weaver, Whitehead, Cotta, Valentine, & Salyers, 1992). Salyers, Arthur, and Kuritza (1981) suggested that Bacteroides thetaiotaomicron could produce acetate, propionate, and succinate by utilizing arabinogalactan.…”
Section: Resultsmentioning
confidence: 99%
“…The relative abundance of Bacteroides ovatus , Bacteroides thetaiotaomicron , Bacteroides cellulosilyticus , and Bacteroides uniformis from genus Bacteroides was significantly higher than that in the control group at the same time point and at 0 hr. Some studies showed that a particular variety of polysaccharides can be fermented by Bacteroides ovatus , Bacteroides thetaiotaomicron , and Bacteroides uniformis (Flint, Scott, Duncan, Louis, & Forano, 2014; Gherardini & Salyers, 1987; Salyers, Vercellotti, West, & Wilkins, 1977; Weaver, Whitehead, Cotta, Valentine, & Salyers, 1992). Salyers, Arthur, and Kuritza (1981) suggested that Bacteroides thetaiotaomicron could produce acetate, propionate, and succinate by utilizing arabinogalactan.…”
Section: Resultsmentioning
confidence: 99%
“…To analyse the importance of this gene cluster for xylan utilization, four different segments of the DNA fragment containing the gene cluster were subsequently cloned into pBT-2, a suicide vector, and used to construct disruptions in the B. ovatus ATCC 8483 chromosome ( Fig. 1A) (Weaver et al, 1992). Insertion of this plasmid results in a duplication of the integrated region, which then flanks the vector sequence, which has an approximate length of 14 kb.…”
Section: Xylan Degradation By Gut-associated Bacteroidetesmentioning
confidence: 99%
“…It is generally believed that only certain species of bacteria from the human colon can utilize AX (for an overview see Grootaert et al 2007). These include Bacteroides ovatus, which possess a xylan utilization operon similar to the one found in the rumen relative Prevotella bryantii (Weaver et al 1992). Among gram-positive species, Roseburia intestinalis utilizes xylans (Chassard and Bernalier-Donadille 2006) and human gut relatives of R. flavefaciens are also likely to degrade and utilize these molecules.…”
Section: Bacteriamentioning
confidence: 99%